2009
DOI: 10.1080/10408440802220603
|View full text |Cite
|
Sign up to set email alerts
|

Non-cancer health effects of diesel exhaust: A critical assessment of recent human and animal toxicological literature

Abstract: We reviewed laboratory and clinical studies bearing on the non-cancer health effects of diesel exhaust (DE) published since the 2002 release of the US EPA Health Assessment Document for Diesel Engine Exhaust. We critically evaluated over 100 published articles on experimental research, focusing on their value for predicting the risk of non-cancer health effects in humans exposed to DE. Human controlled-exposure studies provide new evidence of lung inflammatory effects and thrombogenic and ischemic effects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 135 publications
(325 reference statements)
0
53
0
1
Order By: Relevance
“…Controlled-Exposure Studies As discussed in a previous review, 81 human controlledexposure studies are considered to provide some of the most relevant data for assessing the potential health risks of DE exposure given that they directly study human subjects, use well-defined exposure concentrations and durations, and precisely measure health outcomes including subtle biological responses. We identified only a single peer-reviewed journal publication of human clinical data of relevance to NTDE, as well as two abstracts from the same research team.…”
Section: Preliminary Findings From Humanmentioning
confidence: 99%
“…Controlled-Exposure Studies As discussed in a previous review, 81 human controlledexposure studies are considered to provide some of the most relevant data for assessing the potential health risks of DE exposure given that they directly study human subjects, use well-defined exposure concentrations and durations, and precisely measure health outcomes including subtle biological responses. We identified only a single peer-reviewed journal publication of human clinical data of relevance to NTDE, as well as two abstracts from the same research team.…”
Section: Preliminary Findings From Humanmentioning
confidence: 99%
“…Potential cancer risks remain of interest, but studies involving experimental exposures of humans and animals now focus predominantly on a broad range of noncancer effects (Hesterberg et al 2009; Mauderly and Garshick 2009). …”
mentioning
confidence: 99%
“…Chronic-exposure, animal inhalation studies show a spectrum of dose-dependent inflammation and histopathological changes in the lung in several animal species, including rats, mice, hamsters, and monkeys [3,[25][26]. Human studies have demonstrated exacerbations of chronic bronchitis and chronic obstructive pulmonary disease [17].…”
Section: B Chronic Noncarcinogenic Effectsmentioning
confidence: 99%
“…Diesel exhausts vary significantly in chemical composition and particle size between different engine types (heavy duty vs. light duty), engine operating conditions (idle, accelerate, decelerate) and fuel formulations (high/low sulfur fuels) [8]. Although advances in technology have seen a reduction in the amounts of toxic emissions, toxicologically relevant components (PAH, nitro PAH) persist [3].…”
Section: Diesel Exhaustmentioning
confidence: 99%
See 1 more Smart Citation